The effects of clonal integration and earthworms on the growth, active constituent accumulation in Glechoma longituba, and the soil microbial community in its root zone - Zhao, Bing-Nan; Wang, Xiao-Gai; Zhang, Rui; He, Xue-Ge; Xie, Zi-Yang; Yao, Xiao-Qin; Si, Chao (Frontiers in Plant Science, 2025)
IntroductionClonal integration represents a key ecological advantage of clonal plants, enabling resource transfer among interconnected ramets. Earthworm activity significantly influences soil processes and plant growth. However, it remains unclear whether the effects of earthworms on basal ramets can be transmitted to their apical counterparts through clonal integration.MethodsWe conducted an experiment using Glechoma longituba, a commonly used clonal herb. Basal ramets were either exposed or not exposed to earthworms (Pheretima guillelmi) in the soil, while apical ramets remained devoid of earthworm presence. The stolon connecting the ramets was either severed or left intact.ResultsClonal integration promoted the growth of apical ramets at the expense of basal ramets, resulting in no net gain or loss at the whole fragment level. Although the direct effect of earthworms on plant growth was minimal, they interact with clonal integration to affect the number of nodes and total stolon length. Clonal integration enhanced the accumulation of total flavonoids in the whole fragment, whereas earthworms had a significant negative effect on the accumulation of chlorogenic acid. Clonal integration significantly affected bacterial composition at both basal and apical portions, while concurrently reducing bacterial diversity. Earthworms accumulated specific fungal communities and increased fungal diversity at apical portions. Earthworms also reduced the difference within bacterial communities in the basal portions of both intact and severed treatments to some extent.ConclusionOur findings indicate that clonal integration and earthworms influence the accumulation of active constituents in G. longituba at the whole fragment level, without significantly promoting plant growth. Moreover, earthworms alter the bacterial and fungal communities in the root zone of apical ramets via clonal integration. These results provide a theoretical foundation for the cultivation of this species.